The role of semantic and ontological networks in the digital twin management in manufacturing - Shyshak, Alona; Lutska, Natalia; Vlasenko, Lidia; Pupena, Alexander (My University, 2021)
The paper is devoted to present an overview of the current state of the digital twin development in manufacturing domain in order to determine the place of semantic and ontological networks in digital twin structure. In particular, the current international standards, technical reports and recommendations in the field of Industry 4.0 and Industrial Internet of Things regarding digital twins are considered and analyzed. The article is divided into 3 parts: the first part deals with the concept and main functions of digital twin from different points of view, including standards, the second part concentrates on modern systematized, standardized and applied functions of semantic and ontological networks in industry, in the third part the authors present their vision regarding the role of semantic and ontological networks in the digital twin development and implementation in industry.
Keywords: digital twin; Industry 4.0; Industrial Internet of Things; semantic; ontology; цифровий близнюк; Індустрія 4.0; Промисловий Інтернет речей; семантика; онтологія; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка